A new species of Nyctibatrachus Boulenger (Amphibia: Anura: Nyctibatrachidae) from the surroundings of Bhadra Wildlife Sanctuary, Western Ghats, India - Dinesh, K. P.; Radhakrishnan, C.; Bhatta, Gopalakrishna (Zootaxa, 2008)
A new species of Indian nyctibatrachid frog, Nyctibatrachus dattatreyaensis sp. nov. (Amphibia: Anura), is described from the montane Shola forests of Dattatreya Peeta, Bhadra Wildlife sanctuary, Karnataka, southwestern India, on the basis of unique combination of characters: head wider than long; skin on the dorsum highly wrinkled with transverse corrugated folds; three discontinuous longitudinal folds, one dorsolaterally and two laterally; webbing on toes medium (3/ 4 th ); two yellowish bands on the dorsolateral area, prominent from sub-adult to adult stage; femoral glands present. The largest specimen in the type series has a snout-vent length of 41.0 mm. A revised key to the species of Nyctibatrachus is provided.